USER INTERFACE DESIGN FOR AREA BOUNDARY ARCHIVE APPLICATION OF BANDA ACEH MUNICIPALITY DEVELOPMENT PLANNING AGENCY - Zuhra Sofyan (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims to help the Development Planning Agency of Banda Aceh municipality in developing an online system interface for the data catalog of city boundary records. In addition, this research also aims to find out what functional requirements are needed by the user so the interface design will be able to assist people to store and retrieve the desired data. By using the DIA Cycle method, the interface design able to accommodate the user needs in utilizing the Banda Aceh city boundary catalog data archive system.